Real-time monitoring of cariogenic bacteria via bioluminescent imaging: A biodontic hypothesis - Jafar Kolahi (Wolters Kluwer Medknow Publications, 2016)
Introduction: Dental caries (tooth decay) remains one of the most common chronic infectious disease in the world. Disclosure of camouflaged cariogenic bacteria will be a great motivation for better oral hygiene. The Hypothesis: At present, lux transposon cassette, Tn4001 luxABCDE Kmr, is available that could be used for stable bioluminescent transformation of a wide range of gram-positive bacteria, e.g. Streptococcus mutans and Lactobacillus. After this step, sensitive charge-coupled device (CCD) camera could be used to detect the low levels of light emitted from bioluminescent cariogenic bacteria. Living imaging software would be used for analysis and three-dimensional (3D) reconstruction of images. Evaluation of the Hypothesis: Entrance of transgenic organisms into the oral cavity should be done with great caution. Ethical consideration is necessary and primary animal studies are required. The main limitation of this technique will be oxygen. As mentioned previously, bioluminescent reactions need oxygen. Hence, bioluminescent imaging cannot be used for anaerobic bacteria, e.g., Streptococcus sobrinus.